ROUTINE IMMUNIZATION IN INDIA: A PERSPECTIVE - Taneja, G; Sagar, K S; Mishra, S (Indian Journal of Community Health, 2013)
The Universal Immunization Programme is possibly the longest and one of the biggest public health intervention measures undertaken in India. To improve immunization coverage in the country various initiatives have been undertaken since the inception of the programme in 1985; key inputs being strengthening and expanding the cold chain system, establishing a network of outreach immunization sites, alternate vaccine delivery model, capacity building of health functionaries and medical officers and intensified polio control measures. Introduction of new and underutilized vaccines, drafting of the national vaccine policy, tracking of beneficiaries through the Maternal and Child Tracking system are some of the recent developments. However in spite of more than 25 years since inception the programme is still adversely impacted by challenges across key thematic areas of programme management, cold chain and vaccine management, recording and reporting and injection safety. To further strengthen and improve service delivery 2012-13 has been declared as the “Year of Intensification of Routine Immunization” with the objective of improving immunization coverage rates across poor performing districts and states so as to attain Global Immunization Vision and Strategy goals of 90% coverage at national and more than 80% coverage at district level. Key activities planned during the year include sustained advocacy at all levels, improved communication and social mobilization, robust and regular program reviews, comprehensive microplanning, strengthening cold chain and vaccine logistics system, special catch up rounds through immunization weeks, piloting the teeka express, improved surveillance systems, strengthened partnerships and operational research activities. The current review pertains to the existing scenario of Universal Immunization Program in the country with impetus on the existing challenges, progress achieved till date as a result of various measures and initiatives undertaken and activities lined up as a part of year of intensification of Routine Immunization.